The development, validation and normative data study of the English in Ireland adaption of the Philadelphia repeatable Verbal Learning Test (EirPrVLT-12) for use in an older adult population. (11th September 2020) - Corboy, Holly; Blanco-Campal, Alberto; Bates, Rachel; Bramham, Jessica; Libon, David J.; Greene, Ciara
Abstract: Objective: Cultural adaptations of verbal serial list-learning tests such as the California Verbal Learning Test (CVLT) and the Philadelphia (repeatable) Verbal Learning Test (P(r)VLT) have been shown to be clinically necessary. This paper aimed to culturally adapt, validate and provide normative data for an English in Ireland adaptation of the P(r)VLT, i.e. the EirPrVLT-12, in order to improve episodic memory assessments for Irish adults. Method: EirPrVLT-12 word lists were constructed using a word frequency study of Irish adults ( n  = 58). Two twelve-word, four-trial forms were constructed (standard and alternate form). A normative study included 145 participants who met strict inclusion criteria. Results: EirPrVLT-12 performance varied depending on age, gender, education, estimated IQ and socioeconomic status. Construct validity was established by correlations with other cognitive tests. Principal component analysis yielded a three-factor solution relating to general verbal learning, intrusions and interference. Normed EirPrVLT-12 scaled scores and percentiles stratified by age are available on the Open Science Framework at https://osf.io/vjzsp/, as are regression equations to predict individual scores based on age, gender and education. Conclusions: The data obtained underscores the clinical ultility of the EirPrVLT-12 to assess episodic memory in Irish older adults. Future research was recommended to validate the EirPrVLT-12 in a clinical population, extend normative data to younger populations and develop norms for the alternate form.